Unveiling combining ability and heterotic grouping of newly developed winter maize (Zea mays) inbreds - SINGH, S B; KUMAR, P; KASANA, R K; CHOUDHARY, M; KUMAR, S; KUMAR, R; KARJAGI, C G; KUMAR, B; RAKSHIT, S (The Indian Journal of Agricultural Sciences, 2021)
Pooled analysis of the test-crosses evaluation of 61 newly developed maize (Zea mays L.) inbred lines usingtwo inbred testers namely BML-6 and BML-7 during rabi 2016-17 and 2017-18 at ICAR-IIMR Regional Centre,Begusarai revealed significant variation among genotypes, general combining ability (GCA) and specific combiningability (SCA) effects for all the traits. Out of 61 inbred lines, 29 exhibited significant positive GCA effect for grainyield with maximum GCA effect value of 25.64. Inbred lines, viz. IMLSB-1299-5, IMLSB-406-2, IMLSB-334B-2,IMLSB-814-2 and IMLSB-285-1 were identified as the best general combiners on the basis of GCA effects whichcan be utilized to a greater extent in hybrid breeding programme. Out of 29 inbred lines with significant positive GCAeffects, 12 and 17 lines also showed significant positive SCA effects with tester, BML-7 and BML-6 respectively, thuswere classified into two heterotic groups ‘A’ and ‘B’, respectively. Out of 122 test-crosses, 14 exhibited significantand positive heterosis for yield over three national checks. The information generated on the heterotic grouping willhelp in further streamlining the available germplasm into heterotic pools and thereby augmenting the national hybridbreeding programme.